The Potential of Community Service Activities for the Development of Traditional Bantengan Art-Based Product Businesses in Malang, East Java: Potensi Pengabdian Masyarakat Untuk Pengembangan Usaha Produk Berbasis Seni Tradisional Bantengan Di Malang Jawa Timur - Endah Puspitosarie; Gatot Soebiyakto; Dharmayanti Pri Handini (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Bantengan art is a traditional art that developed in the Malang district of East Java Province. The popularity of art in society provides the potential for the development of art-based products. This article describes the potential for community service for the development of traditional Bantengan art-based product businesses. This potential is an opportunity for community service activities. Activities will benefit art groups and can support preservation efforts. Community service can be carried out to improve knowledge and skills with training methods. Provision of production equipment assistance and mentoring can be carried out for pioneering traditional Bantengan art-based product businesses.